THE ETIOLOGY OF NEUROMUSCULAR FATIGUE INDUCED BY THE 5-M SHUTTLE RUN TEST IN ADULT SOCCER PLAYERS (Kinesiology, 2022)
This study investigated the etiology of neuromuscular fatigue induced by a 5-m shuttle run test (5MSRT) in soccer players. Nineteen adult male amateur soccer players (age: 20.0 ± 2.9 years) participated in the present study. Before and after the 5MSRT, they were instructed to complete a maximal voluntary isometric contraction (MVIC) of the knee extensors (KE) during and after which two electrical stimulations were applied at the femoral nerve. Voluntary activation level (VAL), surface electromyography recordings (sEMG), electrophysiological (Mmax) and potentiated resting twitch (Ptw) responses of the KE were compared between pre- and post-5MSRT. Rating of perception exertion (RPE) was also assessed before, during the test immediately following each sprint repetition and after the test. The distance covered during each sprint significantly decreased as the number of trials performed increased (p